Multiculturalism and Integration A Harmonious Relationship - Clyne, Michael (ANU Press, 2011)
Multiculturalism has been the official policy of all Australian governments (Commonwealth and State) since the 1970s. It has recently been criticised, both in Australia and elsewhere. Integration has been suggested as a better term and policy. Critics suggest it is a reversion to assimilation. However integration has not been rigorously defined and may simply be another form of multiculturalism, which the authors believe to have been vital in sustaining social harmony.